Circadian Regulation of Glutamate Transporters - Chi-Castañeda, Donají; Ortega, Arturo (Frontiers in Endocrinology, 2018)
L-glutamate is the major excitatory amino acid in the mammalian central nervous system. This neurotransmitter is essential for higher brain functions such as learning, cognition and memory. A tight regulation of extra-synaptic glutamate levels is needed to prevent a neurotoxic insult. Glutamate removal from the synaptic cleft is carried out by a family of sodium-dependent high-affinity transporters, collectively known as excitatory amino acid transporters. Dysfunction of glutamate transporters is generally involved in acute neuronal injury and neurodegenerative diseases, so characterizing and understanding the mechanisms that lead to the development of these disorders is an important goal in the design of novel treatments for the neurodegenerative diseases. Increasing evidence indicates glutamate transporters are controlled by the circadian system in direct and indirect manners, so in this contribution we focus on the mechanisms of circadian regulation (transcriptional, translational, post-translational and post-transcriptional regulation) of glutamate transport in neuronal and glial cells, and their consequence in brain function.